63 ÷ 17 = 3 with remainder 12 or 3.71 times.
51 ÷ 3 = 17 Therefore 3 goes into 51 17 times
2 times with a remainder of 3
3, with a remainder of 2.
6 times with a remainder of 3
17
63 ÷ 17 = 3 with remainder 12 or 3.71 times.
57 ÷ 17 = 3 with remainder 6 or 3.35294 times.
37 times with a remainder of 3
Three times.
exactly 17
51 ÷ 3 = 17 Therefore 3 goes into 51 17 times
2 times with a remainder of 3
3, with a remainder of 2.
6 times with a remainder of 3
6 times with a remainder of 3
17 with remainder 3.